الملخص Consciousness Engineering in the Digital Age: Examining the Impact of Cognitive Warfare on Identity Stability among Libyan Youth (Al-Farooq Journal of Sciences, 2026)
This study examines the relationship between exposure to digital environments and the level of identity stability among Libyan youth in the context of the growing influence of cognitive warfare and consciousness engineering. The study adopted a mixed-methods research design, utilizing a stratified random sample of 400 Libyan young men and women, alongside a content analysis of 500 digital materials. The findings revealed a statistically significant positive correlation between media literacy skills and identity stability (r = 0.62, p < 0.01). Furthermore, the content analysis identified the use of sophisticated visual narratives, including memes and short-form video content (Reels), aimed at gradually reshaping cultural references and influencing collective perceptions. The study recommends integrating critical media literacy into university curricula and establishing national digital observatories to monitor and analyze public opinion trends in the digital sphere.
Keywords: Consciousness Engineering, Cognitive Warfare, Identity Stability, Media Literacy, Libyan Youth, Digital Algorithms